Development of a didactical training concept for peer tutors in gross anatomy - Alvarez, Simone; Nikendei, Christoph; Schultz, Jobst-Hendrik (Anatomical sciences education, 2017)
Even though peer tutors are often used in gross anatomy courses, research in the field is rather a subject of the last two decades. This is especially true about the didactical challenges these types of peer tutors experience during their tutorials and about how they are prepared for the task. The aim of the presented study was to learn about the training needs of the tutors, and to subsequently design, implement, and evaluate a didactical training concept. A qualitative design was chosen to examine how tutors can best be prepared for tutorials of gross anatomy. To do so, focus group interviews were conducted. The data were analyzed and grouped into various concepts, using semi-structured interview questions as guidance. It was found that peer tutors are in need of training in the following aspects: Dealing with students who are experiencing difficulties during or as a result of dissection, dealing with group dynamics, that is, at the dissection table, keeping students motivated, time management, and staying confident as a tutor. In order to be regarded as useful and relevant in the eyes of tutors, a preparatory training course should include all these aspects in addition to general didactical training elements. Training needs of peer tutors of gross anatomy go beyond the content of standardized didactical curricula; therefore, tutors should be prepared with a curriculum that is specifically geared toward the many challenges associated with teaching gross anatomy to first year medical students which are already so well documented in the research literature.